Aggression: Health Security Risk Assessment, Prevention Strategies, and Incident Response in Healthcare and Community Settings - Qadh, Yahya Idris Nasser; Salman Fahad Alsharif; Ali Abdullah Aljameeli; Bader Eid Mohammed Aleutayaybi; Badriah Sapeel Alrashidi; Huda Sapeel Alrashidi; Bander Sapeel Alrashidi; Susan Abdulaziz Al-Rafdan; Saleh Khaled Suleiman Al-Habib; Anwar Nawaf Alrashidi; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Aggression and violence in healthcare and community settings pose significant health security risks, impacting patient safety, staff wellbeing, and continuity of care. These behaviors often arise from complex interactions among biological, psychological, and social determinants. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To examine aggression as a multidimensional phenomenon, outline its etiologies, epidemiology, pathophysiology, and propose evidence-based strategies for assessment, prevention, and management. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive review of clinical frameworks, epidemiologic data, and operational protocols was conducted, integrating psychiatric, neurologic, and sociocultural perspectives. The analysis emphasizes structured risk assessment, mental status examination, and interdisciplinary management approaches. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Aggression is frequently linked to psychiatric disorders (e.g., psychosis, bipolar disorder), substance intoxication or withdrawal, neurocognitive decline, and environmental stressors. U.S. data indicate persistent violence burden, with over 1.2 million violent crimes annually and high firearm involvement. Neurobiological findings highlight dysregulation in prefrontal-limbic circuits, serotonergic and dopaminergic pathways, and hormonal influences. Effective management combines early recognition, de-escalation, pharmacologic intervention when indicated, and environmental modifications. Interprofessional collaboration and structured safety protocols significantly reduce escalation and improve outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Aggression is not a singular entity but a transdiagnostic risk state requiring integrated medical, psychiatric, and social interventions. Prevention and treatment strategies must prioritize dynamic risk factors, continuity of care, and staff training to mitigate harm and enhance safety culture.